Generic preference and in-vivo digestibility of alectorioid arboreal lichens by woodland caribou - Rominger, Eric M.; Robbins, Charles T. (Rangifer, 1996)
All caribou exhibited a strong preference (92%) for lichen in the multi-species Bryoria complex (range=87-99%).Preference for Bryoria may be a function of higher protein content, lower tensile strength, or differences in concentrations of secondary plant constituents.